CSRD: the new era of sustainability reporting in Europe - Lampinen, Julia (My University, 2026)
As climate change threatens human well-being and economic stability, companies are in a critical position, as they are both primary emitters and key actors in combating it. In recent years, sustainability reporting has undergone a global shift from voluntary disclosure toward mandatory reporting obligations. The Corporate Sustainability Reporting Directive (CSRD) has positioned the European Union (EU) as a forerunner in sustainability reporting regulation.This thesis aims to describe the main features of the CSRD and examine the underlying reasons for the development of new sustainability reporting legislation in Europe. In addition, this thesis analyzes how the CSRD is expected to directly affect corporate sustainability reporting after the latest amendments introduced in the Omnibus Package. The topic of this thesis is highly timely, as recent changes in sustainability reporting legislation affect thousands of companies across the EU. This thesis was conducted as a literature review. The CSRD entered into force in 2023, requiring certain large companies to prepare sustainability reports in accordance with the European Sustainability Reporting Standards (ESRS) and the principle of double materiality, and to publish them as part of their annual management report. The directive also requires companies to obtain external assurance for the reported information. The objective of the CSRD is to respond to the growing demand for sustainability information and to make reporting practices more efficient and transparent for companies. The Omnibus Package, which entered into force in March 2026, introduced significant changes to sustainability reporting legislation to reduce the administrative burden on companies. For example, the number of companies subject to the CSRD was reduced by approximately 80%. The findings of this thesis indicate that the rationale for developing new sustainability reporting legislation largely stemmed from shortcomings of the previous Non-Financial Reporting Directive (NFRD). The literature identified a gap between stakeholders’ demand for sustainability information and the information companies disclose. Based on the findings, the new sustainability reporting legislation was needed for the EU to achieve its climate objectives, because it requires companies to produce high-quality sustainability reports. Furthermore, the new legislation was also driven by technological requirements and the NFRD's incompatibility with the broader sustainable development legislative framework. Based on the findings of this thesis, the quality of sustainability reports published by companies is expected to improve as a result of the CSRD. At the same time, the number of reporting companies is expected to decrease, likely reducing the overall number of individual sustainability reports.
Keywords: reporting; sustainable development; enterprises; societal responsibility; environmental reporting; corporate responsibility; EU directives; sustainability reporting; legislation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|